2022
DOI: 10.1177/09603271221131307
|View full text |Cite
|
Sign up to set email alerts
|

Has_circ_0010220 regulates the miR-574-3p/IL-6 axis to increase doxorubicin resistance in osteosarcoma

Abstract: Background Osteosarcoma (OS) is the most common primary bone malignancy. It has an aggressive nature and produces drug resistance in diseased patients, which in turn causes obstacles in treating cancer with chemotherapy. The objective of our investigation was to analyze the function and hsa_circ_0010220 mechanism in doxorubicin (DOX) resistance to OS. Methods The hsa_circ_0010220, IL-6, and miR-574-3p levels in OS diseased tissues and cell resistance towards DOX drug were elucidated by qRT-PCR and Elisa assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Moreover, hsa_circ_0010220 can improve the levels of miR-574-3P and IL-6, achieving the goal of resistance to DOX (Gu et al, 2022).…”
Section: Circrnas As Supporters Of Drug Resistance In Osmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, hsa_circ_0010220 can improve the levels of miR-574-3P and IL-6, achieving the goal of resistance to DOX (Gu et al, 2022).…”
Section: Circrnas As Supporters Of Drug Resistance In Osmentioning
confidence: 99%
“…Hsa_circ_0003496 can sponge miR‐370 and subsequently target KLF12 to promote resistance to DOX (Xie, Liang, et al, 2020). Moreover, hsa_circ_0010220 can improve the levels of miR‐574‐3P and IL‐6, achieving the goal of resistance to DOX (Gu et al, 2022).…”
Section: Circrnas Associated With Drug Resistance In Osmentioning
confidence: 99%
“…This may provide new insights into the role of circpvt1 as a biomarker for the diagnosis and treatment of OS. Gu et al 45 showed that has_circ_0010220 increased DOX-resistance in OS by miR-574-3p/IL-6 axis regulation. Reducing DOX resistance in vitro was achieved by silencing Has_circ_0010220.…”
Section: Application Of Circrna In the Diagnosis And Treatment Of Ost...mentioning
confidence: 99%